1971
DOI: 10.1002/pol.1971.150090816
|View full text |Cite
|
Sign up to set email alerts
|

Structure of crystalline polymers with unbranched long side chains

Abstract: The structure and thermodynamic properties of atactic and isotactic acrylic and methacrylic polymers containing 16–18 carbon atoms in the n‐aliphatic side chains, and of copolymers of hexadecyl acrylate with isopropyl acrylate were studied by means of x‐ray and differential thermal analysis. The crystallization of branched acrylic and methacrylic polymers and of acrylic copolymers proceeds in the form of a hexagonal crystal, regardless of the configuration of the backbone chain. Methods of ordering branched ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1

Year Published

1975
1975
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 0 publications
10
84
1
Order By: Relevance
“…From the wide angle values, we found that the side chains of both polymers are tightly packed which has 4.0 Å (and 4.2 Å for fiber samples). It was reported that sidechain polymers having alkyl side groups had a sharp reflection at 4.17 Å when the side chains were long enough to be crystallized in a hexagonal structure [45][46][47][48]. However, bilayered structures with such ordered side chains were not observed on the surfaces of PHEMA#Cs with # 6 13 with shorter alkyl groups.…”
Section: Ft-ir Studymentioning
confidence: 91%
“…From the wide angle values, we found that the side chains of both polymers are tightly packed which has 4.0 Å (and 4.2 Å for fiber samples). It was reported that sidechain polymers having alkyl side groups had a sharp reflection at 4.17 Å when the side chains were long enough to be crystallized in a hexagonal structure [45][46][47][48]. However, bilayered structures with such ordered side chains were not observed on the surfaces of PHEMA#Cs with # 6 13 with shorter alkyl groups.…”
Section: Ft-ir Studymentioning
confidence: 91%
“…Similar effects are found in side-chain polymers, where crystallization is found in poly(n-alkyl methacrylates) having 10 or more methylenes in the side chain. 55 In addition, the amide bands of Glc-NC(n)CN-Glc aggregates showed an odd-even effect for longer chain lengths (n > 11), as shown in Figure 5.12b, indicating bolaamphiphiles with even n had weaker hydrogen bonding between the amide groups than those with odd n. Connecting the amide-linked hydrocarbon bridge to the C2 positions of the glucopyranose rings gave a series of bolaamphiphiles that were far less soluble than their C1-linked counterparts discussed above. 56 However, these bolaamphiphiles (15) showed a similar odd-even effect, with twisted fibers forming for n = 10, 12, 14 and amorphous sheets and ribbons observed for n = 11, 13.…”
Section: Glycolipidsmentioning
confidence: 97%
“…In studying the packing of the long side chains of poly (n-alkyl acrylates), including poly (noctadecyl acrylate), Plate and Shibaev [8] found that the long alkyl chains are extended at right angle to the main chain, while each polymer chain forms a layer structure consisting of rigid 'pivots' (side chains) attached to the main chain and lined up in a regular manner (See Fig 3. inset for poly (n-alkyl acrylates)). Such polymer chains pack in parallel to give a 3D layered ordered structure.…”
Section: Microstructure Of Bsepmentioning
confidence: 99%